2000
DOI: 10.1007/s004410050023
|View full text |Cite
|
Sign up to set email alerts
|

The subcommissural organ of the frog Rana perezi is innervated by nerve fibres containing GABA

Abstract: The innervation of the frog subcommissural organ was studied by light-microscopic and ultrastructural immunocytochemistry using antisera against serotonin, noradrenaline, dopamine, γ-aminobutyric acid (GABA), glutamic acid decarboxylase, different GABA receptor subunits and bovine Reissner's fibre material (AFRU). In the proximity of the organ, serotonin-and noradrenalinecontaining fibres were rare whereas dopamine-immunoreactive fibres were more numerous. Many GABA-and glutamic acid decarboxylase-containing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…More studies in other groups of vertebrates are necessary to determine the evolution of this character due to the large evolution distance between mammals and lampreys. In addition, the cells of the subcommissural organ, a special type of ependymal cells, also lack the GABA B receptor both in lampreys, and in other vertebrates like teleosts, frogs and mammals (Jiménez et al, 2000; Saha et al, 2000; Nürnberger and Schöniger, 2001). Studies in these vertebrates have shown that the GABAergic responses in the subcommissural organ are also mediated by GABA A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…More studies in other groups of vertebrates are necessary to determine the evolution of this character due to the large evolution distance between mammals and lampreys. In addition, the cells of the subcommissural organ, a special type of ependymal cells, also lack the GABA B receptor both in lampreys, and in other vertebrates like teleosts, frogs and mammals (Jiménez et al, 2000; Saha et al, 2000; Nürnberger and Schöniger, 2001). Studies in these vertebrates have shown that the GABAergic responses in the subcommissural organ are also mediated by GABA A receptors.…”
Section: Discussionmentioning
confidence: 99%